2016
DOI: 10.1038/srep32500
|View full text |Cite
|
Sign up to set email alerts
|

Selective Capture of Histidine-tagged Proteins from Cell Lysates Using TEM grids Modified with NTA-Graphene Oxide

Abstract: We report the fabrication of transmission electron microscopy (TEM) grids bearing graphene oxide (GO) sheets that have been modified with Nα, Nα-dicarboxymethyllysine (NTA) and deactivating agents to block non-selective binding between GO-NTA sheets and non-target proteins. The resulting GO-NTA-coated grids with these improved antifouling properties were then used to isolate His6-T7 bacteriophage and His6-GroEL directly from cell lysates. To demonstrate the utility and simplified workflow enabled by these grid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 38 publications
0
46
0
Order By: Relevance
“…For challenging systems and dynamic complexes, the typical path of overexpression, biochemicalscale purification and concentration can be problematic, either because the system cannot be reconstituted, or aggregation may occur. Perhaps even more significant is the disruption of protein structure and protein-protein interactions that can occur when exposed to the air water interface 5 . During the formation of the very thin vitreous ice films (often <50nm) required for high resolution imaging, the very high surface area to volume ratio dramatically increases the probability of exposure to the denaturing interface.…”
mentioning
confidence: 99%
“…For challenging systems and dynamic complexes, the typical path of overexpression, biochemicalscale purification and concentration can be problematic, either because the system cannot be reconstituted, or aggregation may occur. Perhaps even more significant is the disruption of protein structure and protein-protein interactions that can occur when exposed to the air water interface 5 . During the formation of the very thin vitreous ice films (often <50nm) required for high resolution imaging, the very high surface area to volume ratio dramatically increases the probability of exposure to the denaturing interface.…”
mentioning
confidence: 99%
“…One of the strategies for changing interactions of macromolecules with a support, and with the water-air interface, is to chemically modify the molecule itself without changing the chemical properties of the support. Affinity tags chemically modify a protein and have been used in sample preparation for cryoEM in the context of affinity purification (Wang, Liu, et al, 2020, Benjamin, Wright, Bolton, et al, 2016, but as we observed, tag presence can modify interactions with the water-air interface even without the use of affinity grids.…”
Section: Introductionmentioning
confidence: 62%
“…They include using surfactants (Chen et al, 2019, Glaeser et al, 2016, Frederik et al, 1989 to saturate the surface at the water-air interface or the surface of the support (Russo & Passmore, 2014), a graphene oxide or graphene supports to prevent interactions the water-air interface (Pantelic et al, 2010, Pantelic et al, 2011, Wang, Liu, et al, 2020. These supports may also be chemically modified to promote specific, high-affinity interactions with particles (Llaguno et al, 2014, Kelly et al, 2010a, Kelly et al, 2008, Kelly et al, 2010b, Han et al, 2012, Benjamin, Wright, Bolton, et al, 2016, Crucifix et al, 2004, Wang, Liu, et al, 2020, Yeates et al, 2020. Finally, new, fast approaches for depositing samples on a grid have been developed (Arnold et al, 2017, Schmidli et al, 2018, Dandey et al, 2020, Ravelli et al, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…This has successfully been used for the high resolution 3D reconstruction of an icosahedral virus [63]. A similar approach, using Ni-NTA modified grids to capture His-tagged proteins, has also been used to perform “on-grid” purification [64,65], including for smaller protein complexes (Figure 3a). However, both of these techniques can also have limitations.…”
Section: Grid Modification Methods For Specimen Preparationmentioning
confidence: 99%